KEWARISAN BILATERAL ANTARA AHLI WARIS YANG BERBEDA AGAMA DALAM HUKUM PERDATA DAN KOMPILASI HUKUM ISLAM - Ridwan Jamal (IAIN Manado, 2016)
The inheritance in Indonesia commonly uses different law bases, such as civil law, Islamic law, and customary law. Due to religious plurality, the system of inheritance, particularly for those who have different religious background, becomes problematic. This paper will examine how the bilateral inheritance system works in the case of heirs who have different religious beliefs both in civil law and Islamic Law Compilation (KHI) from their testators. It seeks to know and understand the rules and the regulations of how to properly manage rights and obligations of testators and heirs who have different religious beliefs. The Civil law and KHI have different perspectives for this case. The civil law can accommodate the inheritance for those having different religious backgrounds in which the heirs can accept their own rights based on paternal or maternal kinship. The KHI, on other hand, emphasizes that differences in religion can prevent the testator and the heir from inheriting each other. The KHI also stresses that the heirs deserve for the heirdom if they profess Islam before the testators pass away. In other words, the KHI offers a guidance that the similarity of religious belief is the very condition to inherit each other.Keywords: inheritance, different religious background, civil law, Islamic Law Compilation (KHI).